The Importance of Tolerance ValueAs The Foundation of Early Chilhood in Diversity Through Storytelling - Aisya, Nadia (ACIECE, 2018)
One of the basic value that must be possessed by a child to become a human who is able toaccept differences is to have a good religious tolerance attitude in behaving as God’s people,family member, and society member. Early childhood is the best time to embed the tolerancevalue as the foundation in diversity. The importance of this, the golden age developmentperiod in early childhood so this is important that tolerance value is embedded early on,then it can be born a generation that can well tolerate in social, religious, and culturalaspects. This is done as the provision for children to interact in the middle of societydiversity. The differences in ethnicity, religion, and culture will be found in society including inthe school later. Therefore, the understanding of tolerance that has been embedded sincechildhood is very useful as the preparation for children to understand, learn, and get along withtheir environment. By teaching about tolerance can help the children to see that the world theylive in is full of diversity that needs to be appreciated and respected